ANALISIS STRATEGI RETRIBUSI DAERAH SEKTOR PARIWISATA KABUPATEN GOWA - Ardian Leghari; Abd Rakhman Laba; Andi Aswan (JBMI (Jurnal Bisnis, Manajemen, dan Informatika), 2017)
This study aims to generate possible strategies that can be implemented to increase amount of retribution income at the Department of Tourism in Gowa Regency by reviewing 6 tourism objects within the regency. Instruments used for data collection are survey questionnaires, observation, and semi structure interview conducted to 29 respondents comprising of head departments, heads of division, and managements of each tourism object, as well as customers. The collected data were analyzed by using SWOT and IE matrix as a basis for generating possible strategies and determine competitive position of the studied tourism objects. The QSPM is then used to rank the generated strategies for prioritization.  The result of IE matrix showed that the position of the tourism objects is in quadrant V meaning that hold and maintain. The appropriate strategy used is intensive strategy (market penetration and product development). In SWOT matrix analysis, results obtained four alternative strategies, namely: (1) boosting amount of retribution by increasing numbers of tourism objects and supported tourism activities for customer attraction, (2) allocation of human resources in accordance with the competencies, (3) optimizing marketing activities, and (4) increasing awareness for retribution payment. Based on QSPM analysis, an appropriate strategy possibly implemented by Department of Tourism in Gowa Regency is expanding sources of retribution incomes.